If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 2p + -1 = 9p + 4 + -6p Reorder the terms: 3 + -1 + 2p = 9p + 4 + -6p Combine like terms: 3 + -1 = 2 2 + 2p = 9p + 4 + -6p Reorder the terms: 2 + 2p = 4 + 9p + -6p Combine like terms: 9p + -6p = 3p 2 + 2p = 4 + 3p Solving 2 + 2p = 4 + 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 2 + 2p + -3p = 4 + 3p + -3p Combine like terms: 2p + -3p = -1p 2 + -1p = 4 + 3p + -3p Combine like terms: 3p + -3p = 0 2 + -1p = 4 + 0 2 + -1p = 4 Add '-2' to each side of the equation. 2 + -2 + -1p = 4 + -2 Combine like terms: 2 + -2 = 0 0 + -1p = 4 + -2 -1p = 4 + -2 Combine like terms: 4 + -2 = 2 -1p = 2 Divide each side by '-1'. p = -2 Simplifying p = -2
| 4(x-2)+5=2(3x-8) | | 5x-20=.5*12*4x-10 | | 3z+5=4 | | 18+v+2v-8=9v+19-6v-9 | | r^2+17r=-52 | | y=7+18 | | x^4-1296=0 | | 17r*r^2=-52 | | 6v^2+66+60=0 | | 2x+5=10-1x | | 4w^2-19w=5 | | 4-(-66-68)= | | 11-4*14-12= | | 8x+9y-8(6x-4y)= | | -(32m+74n+3)= | | 4.7*-2.3= | | -(z+18)= | | 15u+12+20u+40= | | 3x^2=8-7x | | 4a^2+12a+9=144 | | 998+9= | | 3x-x= | | 17d-12d= | | -4X+5Y=33 | | -5.05*-2= | | -(2x+4)-(x-5)= | | 10-5m=20 | | 3x^2-12x+3=x^2-4 | | -3/4*(-6/7)= | | 8*-6= | | 2(x+3)-(3x-5)= | | x^6-152x^3+3375=0 |